1.1 GBIT/S white lighting LED‐based visible light link with pulse amplitude modulation and Volterra DFE equalization. Issue 7 (July 2015) - Stepniak, Grzegorz; Maksymiuk, Lukasz; Siuzdak, Jerzy
ABSTRACT We report a visible light communication link that uses a white phosphorescent LED as transmitter and a p‐i‐n photodiode combined with blue optical filter as a receiver. Multilevel pulse amplitude modulation (PAM) is used for data transmission. It is shown that a receiver with a decision feedback equalizer and nonlinear second‐order Volterra feed‐forward section allows for 1.1 Gbit/s throughput at BER = 10–3 when used with PAM‐4. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1620–1622, 2015